Is the likelihood of spousal violence lower or higher among childless women? Evidence from Nigeria demographic and health surveys - Bola Lukman Solanke; Adeleke Luqman Bisiriyu; Amos Oyedokun (BMC Women's Health, 2018)
Abstract Background Few studies have been able to determine whether the likelihood of spousal violence is higher or lower among childless women compared with women who have children. This is because most studies linking childlessness and spousal violence were either qualitative or were conducted among childless women attending fertility clinics. In the fewer quantitative studies that linked childlessness and spousal violence, results are mixed and yet to be verified in Nigeria using nationally representative sample data. The current study addresses this knowledge gap by raising the research question: is the likelihood of spousal violence lower or higher among childless women? Methods The study analysed data from 2008 and 2013 Nigeria Demographic and Health Surveys. Only women aged 35–49 years are included in the analysis. The outcome variable was spousal violence, while the key explanatory variable was parity status categorised into childless, have only one child, and have two or more children. Selected individual-level and community-level variables were included as additional explanatory variables. The multilevel mixed-effects logistic regression analysis was applied in four nested models using Stata 12. Results In Model 1, result show 57% more likelihood of spousal violence among women who have two or more children compared with childless women (OR = 1.570: CI: 1.074–2.294). In Model 2, women who have two or more children were 52.3% more likely to experience spousal violence compared with childless women (OR = 1.523; CI: 1.037–2.247). In Model 3, the likelihood of spousal violence was 67.2% higher among women who have two or more children compared with childless women (OR = 1.672; CI: 1.140–2.452). In the full model, women who have two or more children were 50.8% more likely to experience spousal violence compared with childless women (OR = 1.508; CI: 1.077–2.234). The Intra-Class Correlation (ICC) provides evidence to support community contributions to prevalence of spousal violence. Conclusions The likelihood of spousal violence is lower among childless women in Nigeria. Causes of spousal violence against women cut across individual, family, and community characteristics irrespective of childlessness or number of children. Current Behaviour Change Communication should be strengthened by adequate enforcement of the newly enacted Violence Against Persons (Prohibition) Act of 2015.